Spotted owls - Neuenfeldt, Elizabeth (Bellwether Media, Inc., 2024)
"Relevant images match informative text in this introduction to spotted owls. Intended for students in kindergarten through third grade"--
Includes bibliographical references and index.
Ages 5-8
Grades 2-3
Keywords: Spotted owl -- Juvenile literature